2017
DOI: 10.1158/0008-5472.can-17-0701
|View full text |Cite
|
Sign up to set email alerts
|

Infection Exposure PromotesETV6-RUNX1Precursor B-cell Leukemia via Impaired H3K4 Demethylases

Abstract: ETV6-RUNX1 is associated with the most common subtype of childhood leukemia. As few ETV6-RUNX1 carriers develop precursor B-cell acute lymphocytic leukemia (pB-ALL), the underlying genetic basis for development of full-blown leukemia remains to be identified, but the appearance of leukemia cases in timespace clusters keeps infection as a potential causal factor. Here, we present in vivo genetic evidence mechanistically connecting preleukemic ETV6-RUNX1 expression in hematopoetic stem cells/precursor cells (HSC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
98
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(109 citation statements)
references
References 45 publications
6
98
0
3
Order By: Relevance
“…This is only possible if the oncogenic event(s) have an inherent reprogramming capacity and the leukemia-initiating cell has the necessary plasticity (Sanchez-Garcia, 2015). Several prior studies have been involved in studying aberrations in HSC/PC as an important driver for myeloid and Bcell hematopoietic neoplasms through a reprogramming mechanism (Perez-Caro et al, 2009;Vicente-Duenas et al, 2012a,c;Green et al, 2014;Rodriguez-Hernandez et al, 2017), but to our knowledge, there is no evidence that a similar mechanism may be relevant for T-ALL. Two alternative explanations can be contemplated to interpret the close association existing between the LMO2 oncogene and human T-ALL development: on the one side, the classical interpretation that considers that the role of LMO2 as the T-ALL-initiating genetic alteration takes place in a committed/differentiated target T cell.…”
Section: Discussionmentioning
confidence: 99%
“…This is only possible if the oncogenic event(s) have an inherent reprogramming capacity and the leukemia-initiating cell has the necessary plasticity (Sanchez-Garcia, 2015). Several prior studies have been involved in studying aberrations in HSC/PC as an important driver for myeloid and Bcell hematopoietic neoplasms through a reprogramming mechanism (Perez-Caro et al, 2009;Vicente-Duenas et al, 2012a,c;Green et al, 2014;Rodriguez-Hernandez et al, 2017), but to our knowledge, there is no evidence that a similar mechanism may be relevant for T-ALL. Two alternative explanations can be contemplated to interpret the close association existing between the LMO2 oncogene and human T-ALL development: on the one side, the classical interpretation that considers that the role of LMO2 as the T-ALL-initiating genetic alteration takes place in a committed/differentiated target T cell.…”
Section: Discussionmentioning
confidence: 99%
“…Additional alterations to this hypothesis have been made, including delayed infection [22] and population mixing [23]. Recent studies have provided in vivo evidence by linking ALL in Pax5-heterozygous mice [24] and ETV6-RUNX1 + mice [25] to exposure to infection. The exact mechanisms of leukemic transformation through infection are not yet fully understood, but dysregulation of the immune system may play a major role.…”
Section: Mechanisms Of Transformationmentioning
confidence: 99%
“…Furthermore, the mixing of populations has been postulated as a causal factor for leukemic transformation [23]. Recent studies have shown that exposure to infection can trigger the progression from preleukemia to ALL [24,25]. A dysregulated immune response by activation of preleukemic B cells through memory T helper cells [26] and inactivity of NK cells have also been discussed [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the frequency of preleukemic cells in healthy blood or cord blood was controversially discussed, ranging from ,10 25 to 10 23 . [21][22][23][24][25] Asterisks mark the breakpoint present in the REH cell line. The breakpoints identified in the present study are indicated by orange (N424), blue (N726), red (N817), green (N823), and yellow (N890) arrows.…”
mentioning
confidence: 99%